Atypical Clinical Manifestations of Graves' Disease: An Analysis in Depth. (1st November 2011) - Hegazi, Mohamed Osama; Ahmed, Sherif
Abstract : Over the past few decades, there has been an increase in the number of reports about newly recognized (atypical or unusual) manifestations of Graves' disease (GD), that are related to various body systems. One of these manifestations is sometimes the main presenting feature of GD. Some of the atypical manifestations are specifically related to GD, while others are also similarly seen in patients with other forms of hyperthyroidism. Lack of knowledge of the association between these findings and GD may lead to delay in diagnosis, misdiagnosis, or unnecessary investigations. The atypical clinical presentations of GD include anemia, vomiting, jaundice, and right heart failure. There is one type of anemia that is not explained by any of the known etiological factors and responds well to hyperthyroidism treatment. This type of anemia resembles anemia of chronic disease and may be termed GD anemia. Other forms of anemia that are associated with GD include pernicious anemia, iron deficiency anemia of celiac disease, and autoimmune hemolytic anemia. Vomiting has been reported as a presenting feature of Graves' disease. Some cases had the typical findings of hyperthyroidism initially masked, and the vomiting did not improve until hyperthyroidism has been detected and treated. Hyperthyroidism may present with jaundice, and on the other hand, deep jaundice may develop with the onset of overt hyperthyroidism in previously compensated chronic liver disease patients. Pulmonary hypertension is reported to be associated with GD and to respond to its treatment. GD-related pulmonary hypertension may be so severe to produce isolated right-sided heart failure that is occasionally found as the presenting manifestation of GD.